Analysis of the Impact and Bending Strength of Coconut Coir Fiber-Reinforced Polyester Resin Composite Material for Automotive Bumper Applications - Lalu Moch Syarif Hidayatullah; Anggit Murdani (International journal of technology and education research, 2026)
The automotive industry requires lightweight, durable, cost-effective, and environmentally friendly materials to improve vehicle performance and sustainability. This study investigates the effect of coconut coir fiber volume fraction and fiber orientation on the impact and flexural strength of polyester matrix composites intended for automotive bumper applications. Composite specimens were fabricated using the hand lay-up method with three fiber orientations: random, unidirectional, and laminated. Impact and flexural tests were conducted according to ASTM standards, and the experimental data were analyzed using Two-Way ANOVA. The results revealed that fiber volume fraction significantly affected impact strength (p = 0.043 < 0.05), indicating that higher fiber content improved the composite's ability to absorb impact energy. In contrast, fiber orientation and the interaction between fiber volume fraction and fiber orientation showed no significant effect on impact strength. Furthermore, neither fiber volume fraction, fiber orientation, nor their interaction significantly influenced flexural strength (p > 0.05). These findings demonstrate that fiber volume fraction is the dominant factor affecting the impact performance of coconut coir fiber-reinforced polyester composites. Therefore, the developed composite shows promising potential as a sustainable alternative material for automotive bumper applications.